ANALISIS PENERAPAN PSAP NOMOR 13 TENTANG PENYAJIAN LAPORAN KEUANGAN BADAN LAYANAN UMUM PADA PUSKESMAS TOLANGOHULA - Yusuf, Fitria; Makur, Dharmawaty; Tuliabu, Alvina (JSAP : Journal Syariah and Accounting Public, 2023)
The research aims to obtain answers to the problems formulated, namely to find out the presentation of the financial reports of the public service agency of the Tolangohula Health Center in accordance with PSAP No. 13 and what obstacles are encountered in implementing PSAP number 13. The research uses a qualitative approach, through conducting interviews and documentation at the research location. The research results showed  the application of PSAP Number 13 at the BLUD Tolanghula Health Center, when viewed from the financial reports: Budget realization report (LRA), report on changes in excess budget balance (LPSAL), balance sheet, operational report (LO), cash flow report, report on changes in equity and notes on financial statements are in accordance with government accounting standard number 13. However, the Puskesmas Tolangohula is lack of  understanding of the human resources about PSAP No. 13.